Thiotriazoline ointment effects modification by incorporating silver nanoparticles in experimental thermal burns - Grin, I. V.; Zvyagintsevа, T. V.; Naumova, O. V.; Grin, V. V. (Journal of Education, Health and Sport, 2016)
Grin I. V., Zvyagintsevа T. V., Naumova O. V., Grin V. V. Thiotriazoline ointment effects modification by incorporating silver nanoparticles in experimental thermal burns. Journal of Education, Health and Sport. 2016;6(12):916-928. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.268951 http://ojs.ukw.edu.pl/index.php/johs/article/view/4241 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 25.12.2016. UDK: 615.27:615.31:546.57-022.532:616-001.17-092.9 Thiotriazoline ointment effects modification by incorporating silver nanoparticles in experimental thermal burns I. V. Grin, T. V. Zvyagintsevа, O. V. Naumova, V. V. Grin Kharkiv National Medical University, Kharkov, Ukraine iscil9uwa9@mail.ru Abstract We evaluated Thiotriazoline ointment effects modification by incorporating silver nanoparticles in experimental thermal burns. Studies were carried out on 78 rat population WAG (4 groups, each group of 6 rats): 1 – intact; 2 – burn (without treatment), 3 – burn + "Thiotriazoline ointment 2%", the reference drug; 4 – burn + Thiotriazoline ointment with silver nanoparticles (0.00081%). We studied the skin morphological changes upon thermal damage. We have found that the incorporation of silver nanoparticles in Thiotriazoline ointment modifies its healing action; reparative process takes place more intensively than with Thiotriazoline ointments, which is confirmed by destructive process restriction within epidermis and derma, epithelialization acceleration and complete closure of the defect at 21th day of thermal burn healing versus 28th day with reference drug use. Keywords: Thiotriazoline ointment with silver nanoparticles, thermal burns.